HADIS MAUDHU’ DAN PERMASALAHANNYA - Dr. Mukhlis Mukhtar (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2017)
Hadith maudhu or false hadith is leaning against something to the prophet of Allah saw., whereas he himself never say, do, or set. Forgery traditions arise due to: a) political disputes, b) maneuver enemies of Islam, c) primordialism and chauvinism, d) fanaticism schools and kalam, e) the cult of the individual, f) maker of the story, g) approaches to the authorities, and h) the desire to do good without the basic knowledge of religion. As for the hadith maudhu’ traits among others, there qarinah indicating that the narrators was not met with a person who is recognized as a teacher, there is confusion on matn, its meaning can not make sense and is contradictory to the passage of the Koran. Discussion of hadith maudhu’ 'is very important, because of counterfeiting activities tradition has become a reality in history, also mainly in order to maintain the purity of traditions of the Prophet and prevent Muslims from the mistake and is caught in the practice of the hadith maudhu